Beyond (Just) the Workplace: A Theory of Leader Development Across Multiple Domains - Hammond, Michelle; Clapp-Smith, Rachel; Palanski, Michael (Academy of Management Review, 2017)
Most leaders develop through experiences across multiple domains of life (work, community, friends/family), yet how this process occurs remains largely unexplored. We propose a theory to explain how leaders develop across multiple domains by explicating both the process and content of leader development. Using a sensemaking framework, we describe how leaders first notice and subsequently interpret cross-domain connections and disconnections, leading to changes in their identity with respect to strength, integration, meaning, and level. These changes then lead to increased depth and breadth of leader competence and an ongoing, interweaving process of sensemaking that explains cross-domain leader development. We conclude with a discussion of the benefits of and future directions for studying leader development across domains for leaders, organizations, and leadership educators.